Pengembangan “Majeda” Berbasis Dolanan Anak untuk Pengoptimalan Tumbuh Kembang Siswa Taman Kanak-kanak - Wawan Sundawan Suherman (Jurnal Cakrawala Pendidikan, 2017)
This research aims to develop a "model of educative and attractive physical activity" (Majeda) based on children play as a mean for optimize kindergarteners’ growth and development. This research was using research and development of Borg and Gall. The research will be conducted in three stages: developing model, pilotting models, and the operational testing and dissemination of models. First phase of research to develop the model implemented by the following activities: preparing the model design, reviewing aspects of the teaching learning process in kindergarten, characteristics of kindergarterners, and the values and elements of motion in children play, choosing the format of Majeda, and validating the draft of Majeda. The result of analysis showed that the design of Majeda based on children play can be arranged, then validated by experts and practitioners.